Eradication of frambusia of Kedungjati Health Center in 2023 - Harmoni, Pratiwi Hesti; Musabaqoh, Hidayatul (Institute of Computer Science (IOCS), 2025)
Frambusia is a tropical disease that affects children. Frambusia diagnosis is based on clinical and serologic examination. The purpose of this service is to find out that there are no cases of frambusia in Kedungjati District. The method of service carried out was education, screening of all elementary school students, and RDT Frambusia examination. Before the screening, students were educated on the definition of frambusia, causes and risk factors, and how to prevent frambusia. Screening, body examination was conducted on all students present. Students were examined from head to toe, to look for scabs or frambusia lesions. If scabs or frambusia lesions are found, a Frambusia Rapid Diagnostic Test will be conducted. If a positive case is found, treatment will be given at the health center. The conclusion of this activity is that no frambusia cases were found in Kedungjati Sub-district. Advice to the community is to know the factors that play a role in maintaining zero cases of frambusi. Background: Frambusia is a tropical disease that primarily affects children in developing countries. It is characterized by skin lesions and can lead to disfigurement if left untreated. Early detection and treatment are crucial for preventing the spread of frambusia and maintaining public health in endemic areas. Methods:The method involved three main components: education, screening, and diagnostic testing. Students were first educated about frambusia, including its definition, causes, risk factors, and prevention. This was followed by a comprehensive physical examination of all present elementary school students, checking for frambusia lesions or scabs. If suspicious lesions were found, a Rapid Diagnostic Test (RDT) for frambusia was conducted, with positive cases to be treated at the local health center. Results: The result of this service activity was that no cases of frambusia were found in Kedungjati District. The screening and examination of all present elementary school students did not reveal any frambusia lesions or positive Rapid Diagnostic Test results. Conclusion: No frambusia cases were found in Kedungjati Sub-district. It is recommended that the community be informed about the factors that contribute to maintaining zero cases of frambusia in the area.